Models Help to Provide 24/7 Radiology Coverage in Academic Medical Centers - Nichols, Emma Hitt (MD Conference Express, 2015)
There is increasing demand for round-the-clock radiology coverage in academic medical centers, which poses a range of challenges. In this session, presenters reviewed the issues of staffing including scheduling and staff retention, clinical coverage, resident autonomy and training, financial considerations, and balancing clinical needs with academic demands.